Chapter 6 Beyond curses In the midst of turbulent Kyzyl - Stelmaszyk, Mally (Taylor & Francis, 2022)
Instead of merely recapitulating the main chapter findings, the conclusion expands dynamically on the themes of curses and shamanism by focusing on wider sociocultural processes and shifts occurring in post-Soviet Kyzyl. In short, it highlights how the way people experience and describe post-Soviet life in Kyzyl is similar to the way people who have been cursed describe and experience this phenomenon, suggesting that day-to-day life in Kyzyl could be compared to living a curse. In fact, emphasising the role of turbulence, shock and uncertainty associated with cursing, the chapter concentrates on different representations of post-colonial conflicts, such as tensions between individual shamans and shamans from the societies, shifts in the religious and family landscapes, alcoholism, disease and technological development. More than this the chapter delineates how the shifts occurring in post-Soviet Kyzyl can be effectively analysed without reverting to the already exhausted ideas about cultural revivalism and ethnic rediscovery, dominant in the studies of the post-colonial sociocultural landscapes.